2021
DOI: 10.48550/arxiv.2103.12600
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiplicity of solutions for fractional $q(.)$-Laplacian equations

Abstract: In this paper, we deal with the following elliptic type problemwhere q(.) : Ω × Ω → R is a measurable function and s(.) : R n × R n → (0, 1) is a continuous function, n > q(x, y)s(x, y) for all (x, y) ∈ Ω × Ω, (−∆) s(.) q(.) is the variable-order fractional Laplace operator, and V is a positive continuous potential. Using the mountain pass category theorem and Ekeland's variational principle, we obtain the existence of a least two different solutions for all λ > 0. Besides, we prove that these solutions conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Variable-order fractional Laplacian. In some recent contributions ( [7,10,79,95]), elliptic problems involving a variable-order fractional Laplacian (that is, with s = s(x) : Ω → (0, 1)) have been considered, analyzing the existence of (possible several) solutions and some optimal control issues applied to image denoising. It would be of interest to investigate parabolic problems (which,as far as we can tell, are still unaddressed) and associated theoretical and numerical control problems.…”
Section: Conclusion and Open Problemsmentioning
confidence: 99%
“…Variable-order fractional Laplacian. In some recent contributions ( [7,10,79,95]), elliptic problems involving a variable-order fractional Laplacian (that is, with s = s(x) : Ω → (0, 1)) have been considered, analyzing the existence of (possible several) solutions and some optimal control issues applied to image denoising. It would be of interest to investigate parabolic problems (which,as far as we can tell, are still unaddressed) and associated theoretical and numerical control problems.…”
Section: Conclusion and Open Problemsmentioning
confidence: 99%
“…Their results were obtained using the MPT and Ekeland's variational principle. Finally, several open and interesting problems about the existence and multiplicity of solutions were highlighted at the end of their paper [47] (see of the aforementioned recent related works [41,[43][44][45][46] on the same subject).…”
Section: Introductionmentioning
confidence: 96%
“…In 2021, Rahmoune and Biccari [47] investigated a multiplicity of solutions for the fractional Laplacian operator involving variable exponent nonlinearities of the type…”
Section: Introductionmentioning
confidence: 99%
“…An important operator for posing fractional partial differential equations (FPDEs) is the fractional Laplacian, which has many equivalent definitions [7] although it is most commonly introduced using Fourier and inverse Fourier transforms. Detailed introductions and studies of the fractional Laplacian can be found in [8,9] and the references therein, while some related operators and extensions are studied for example in [10,11].…”
Section: Introductionmentioning
confidence: 99%